Bureaucracy: Max Weber’s concept and its application to Pakistan - Arshad Islam, Islam (David Publisher, 2018)
To investigate Max Weber’s concept of bureaucracy and its relevance to Pakistan’s civil service, this study explains the system of governance followed in different nations, its function, and bureaucratic formulations in the well-managed and administered state. The paper analyzes reasons for the poor performance of Pakistani public service provision. International development doctrines pertaining to governance are based on accountable to the governments and effective bureaucracy. This study explores the formation of the Pakistani state and civil service and its role in the implementation of government policies. Irrespective of the system of governance followed across different nations, the presence, and functioning of a bureaucratic set-up is crucial to manage and administer the state. However, in Pakistan there has been an egregious failure of the bureaucratic set-up to achieve this vision. This study explores the reasons why based on Weberian sociological theory affirming that the main characteristic of bureaucracy is espirit de corps, doing things for the good of the institution (i.e., civil service) even if goes against the public interest. This study analyzes such orientation in the context of a major developing state, Pakistan. The essential principal function of bureaucracy is to honestly and sincerely implement the government policies on behalf of the people. The government provides representation of the national interest, mainly when democratically elected, while the bureaucracy provides skills and know-how; the latter is liable to the former, but often not directly to the public. Thus, bureaucrats are usually known as “civil servants”, who provide continuity in governance and daily life, despite the vagaries of changes in government. This is a qualitative research entirely based on literature survey from library data collected from books and articles.